Soil chemistry. - Strawn, Daniel; Bohn, Hinrich L., 1934-; O'Connor, George A., 1944- (John Wiley & Sons, 2020)
"The topics covered in Soil Chemistry, Fourth Edition, are presented in the same order as previous versions. We have added a chapter on surface charge properties (Chapter 9), and the adsorption chapters of the previous editions have been completely reorganized-explanation of cation, anion, and organic chemical adsorption processes are presented in Chapter 10, and quantitative modeling of adsorption processes is presented in Chapter 11. New to this version are special topics boxes that provide highlights of topics, historical information, and examples. Enhanced discussion of carbon cycling, new theories of SOM formation and structure, details of soil redox properties, and information on chemicals of emerging concern have been added. In each chapter, key words are bolded; students should use key words as study aides to ensure they understand main concepts"--